2019
DOI: 10.1002/brb3.1408
|View full text |Cite
|
Sign up to set email alerts
|

The role of the brain–gut–microbiota axis in psychology: The importance of considering gut microbiota in the development, perpetuation, and treatment of psychological disorders

Abstract: IntroductionThe prevalence of psychological disorders remains stable despite steady increases in pharmacological treatments suggesting the need for auxiliary treatment options. Consideration of the brain–gut–microbiota axis (BGMA) has made inroads into reconceptualizing psychological illness from a more holistic perspective. While our understanding of the precise role of gut microbiota (GM) in psychological illness is in its infancy, it represents an attractive target for novel interventions.MethodAn extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 256 publications
0
27
0
5
Order By: Relevance
“…Similar to obesity, psychological conditions have been associated with inflammatory processes and dysbiosis in the GI microbiota [ 19 , 20 ]. Communication via the gut–brain axis is bidirectional and conducted through a complex network including the central nervous system (CNS), enteric nervous system and endocrine and immune systems [ 21 ]. The effects of the microbiota on brain development, psychological conditions and host behavior have attracted the attention of researchers over the last decade [ 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to obesity, psychological conditions have been associated with inflammatory processes and dysbiosis in the GI microbiota [ 19 , 20 ]. Communication via the gut–brain axis is bidirectional and conducted through a complex network including the central nervous system (CNS), enteric nervous system and endocrine and immune systems [ 21 ]. The effects of the microbiota on brain development, psychological conditions and host behavior have attracted the attention of researchers over the last decade [ 19 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal parasites alter the intestinal physiology, cause chronic intestinal inflammation [28], and impact on the microbiota-gut-brain axis [27,[29][30][31]. The gut microbiome affects brain function by changing immunological mechanisms, causing inflammation, and modifying the functions of several neurotransmitters [32][33][34][35][36]. Recent studies have also suggested that the intestinal microbiome plays a role in neurodevelopmental and neurobehavioral conditions [31,32,37], and some clues exist about their association with personality traits [33] and psychological symptoms [36].…”
Section: Introductionmentioning
confidence: 99%
“…В рамках недостающего звена в понимании патогенеза деменции рассматривается качественное и количественное изменение кишечной микробиоты (КМ). Современные исследования оси мозг-кишечник-микробиота демонстрируют, что психологические дисциплины находятся на пороге значительного сдвига парадигмы, отходя от ЦНС-центрического к междисциплинарному подходу [12,13]. Микробиота желудочно-кишечного тракта (ЖКТ) играет большую роль в физиологическом гомеостазе и метаболизме организма человек, выполняя огромное количество жизненно важных функций: морфокинетическую, ферментативную, иммуномодулирующую, обеспечение колонизационной резистентности и т. д. Не случайно некоторые авторы называют КМ «забытым органом» [14].…”
unclassified
“…Микробиота желудочно-кишечного тракта (ЖКТ) играет большую роль в физиологическом гомеостазе и метаболизме организма человек, выполняя огромное количество жизненно важных функций: морфокинетическую, ферментативную, иммуномодулирующую, обеспечение колонизационной резистентности и т. д. Не случайно некоторые авторы называют КМ «забытым органом» [14]. Новые исследования показывают, что КМ напрямую связана с патогенезом деменции, вызывая метаболические нарушения и прогрессирование низкодифференцированного воспаления [12], что позволяют рассмотреть современную более эффективную стратегию лечения и профилактики деменции путем модуляции микробиоты (например, с использованием диетических рекомендаций или применения пре-и пробиотиков).…”
unclassified
See 1 more Smart Citation